2013
DOI: 10.1007/s12011-013-9722-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Long-Term Intermittent Hypobaric Hypoxia on Bone Mineral Density in Rats: Role of Nitric Oxide

Abstract: Intermittent hypoxia is the most common pattern of hypoxic exposure in humans. The effect of chronic long-term intermittent hypobaric hypoxia (CLTIHH) on bone metabolism is not investigated. We examined the effect of CLTIHH on bone metabolism and the role of nitric oxide (NO) in this process. The rats were divided into three groups in this study. The animals in groups I and II have been exposed to CLTIHH. The animals in group II were also treated with nitric oxide synthase inhibitor NG-nitro-L-arginine methyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…Cyclic exposure appears to produce varying responses. One study has reported improvements in structural measures of bone following 5 weeks of exposure of 4,500 m, lasting 5 hr a day for 5 days a week (Guner et al, 2013). Yet, others have noted that less severe exposures are unable to yield similar responses (Camacho‐Cardenosa, Camacho‐Cardenosa, Burtscher, et al, 2019; Martínez‐Guardado et al, 2019; Ramos‐Campo, Rubio Arias, & Jimenez Diaz, 2015).…”
Section: In Vivo Hypoxiamentioning
confidence: 99%
“…Cyclic exposure appears to produce varying responses. One study has reported improvements in structural measures of bone following 5 weeks of exposure of 4,500 m, lasting 5 hr a day for 5 days a week (Guner et al, 2013). Yet, others have noted that less severe exposures are unable to yield similar responses (Camacho‐Cardenosa, Camacho‐Cardenosa, Burtscher, et al, 2019; Martínez‐Guardado et al, 2019; Ramos‐Campo, Rubio Arias, & Jimenez Diaz, 2015).…”
Section: In Vivo Hypoxiamentioning
confidence: 99%
“…Much of this data comes from simulated hypoxia in rats; the effect of hypoxia on bone cells in humans may ultimately depend on the duration, severity, frequency, and chronicity of the hypoxia …”
Section: Direct and Indirect Mechanisms By Which Osa May Affect Bonementioning
confidence: 99%
“…(81) Much of this data comes from simulated hypoxia in rats; the effect of hypoxia on bone cells in humans may ultimately depend on the duration, severity, frequency, and chronicity of the hypoxia. (83) Sleep fragmentation, sleep deficiency, and bone Recurrent awakenings occur throughout the night in those affected by OSA, resulting in the buildup of sleep loss or sleep "debt." Although the amount of sleep required by an individual varies, evidence suggests physiologic and neurobehavioral deficits are more likely with less than 7 hours of sleep per night.…”
Section: Hypoxia and Bonementioning
confidence: 99%
“…19 IH protocol was found to increase BMD values in rats in a study for 5 days/week for 5 weeks. 20 Torres et al reported that IH (6 h/day for 32 days) model in a mouse model did not significantly modify BMD and concluded that IH preserved BMD in their mouse model. 21 Adding to that, the presence of underlying conditions such as hypertension or obesity, as well as age, sex, or genotypic variance may be important factors tilting the balance between an appropriate homeostatic response and decompensation.…”
Section: Discussionmentioning
confidence: 97%
“…The adaptive or mal‐adaptive responses can be generally predicted by the frequency, severity and duration of IH . IH protocol was found to increase BMD values in rats in a study for 5 days/week for 5 weeks . Torres et al .…”
Section: Discussionmentioning
confidence: 99%